The Effect of Competence and Independence on the Audit Quality of Tomohon City Inspectorate Apparatus - Evinita, Lenny Leorina; Kawulur, Arie Frits; Rosari, Meilian (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2024)
Based on the results of audit quality as a process in which Tomohon City inspectorate officials must find and report violations in the accounting system based on their knowledge and skill. However, there are indications that there were audit findings that were not detected by Tomohon City inspectorate officials as internal auditors, but were discovered by the Indonesian Financial Audit Agency (BPK) as external auditors. This research aims to determine the influence of competence and independence on the audit quality of Tomohon City inspectorate officials. This research uses primary data obtained from distributing questionnaires to all inspectorate apparatus who took part in inspection duties, namely 36 people. The sample selection method for this research uses a census sampling method. The data analysis technique used is multiple linear regression analysis using the SPSS Statistics 29 program. The results of this research show that partially the competency variable has a negative and significant effect on audit quality, while the independence variable has a positive and significant effect on audit quality. Then simultaneously or together the competency and independence variables have a significant effect on audit quality.